Digitalisasi QRIS, BI-Fast, dan APBN dalam Mendukung Kebijakan Moneter dan Fiskal Indonesia - Azmal Hali; Halimahtus Sadiah; Zahra Devina Dewi; Muhammad Zhafran Syahputra; Valendra Desilva; Ahmad Setiawan Nuraya (CV. ITTC INDONESIA, 2025)
This research focuses on the implementation of the QRIS payment system, BI-Fast services, and the digitalization of the management of the State Budget (APBN) through SPAN, as well as how digitalization aids the success of monetary and fiscal policies in Indonesia. The lives of the Indonesian people are now significantly influenced by digital transformation in recent years, which has helped to increase household consumption and the economic resilience of the country. This study employs descriptive qualitative research aimed at analyzing the impact of digitalization on the effectiveness of macroeconomic policies, both monetary and fiscal. Descriptive research was chosen because this study focuses on explaining phenomena rather than seeking associations between variables. The results indicate that the implementation of digital payment systems has improved financial inclusion, transaction efficiency, and transparency in the management of the state budget. Despite challenges in implementation, such as lengthy bureaucracy and the potential for budget misuse, digitalization through SPAN is expected to accelerate the payment and disbursement processes. Future research will focus on exploring social impacts, investigating effective collaborations, and creating a digital ecosystem.